Finite rings
Content created by Fredrik Bakke, Egbert Rijke and Victor Blanchi.
Created on 2023-05-25.
Last modified on 2025-02-11.
module finite-algebra.finite-rings where
Imports
open import elementary-number-theory.addition-natural-numbers open import elementary-number-theory.natural-numbers open import finite-group-theory.finite-abelian-groups open import finite-group-theory.finite-groups open import finite-group-theory.finite-monoids open import foundation.binary-embeddings open import foundation.binary-equivalences open import foundation.embeddings open import foundation.equivalences open import foundation.identity-types open import foundation.injective-maps open import foundation.involutions open import foundation.propositions open import foundation.sets open import foundation.unital-binary-operations open import foundation.universe-levels open import group-theory.abelian-groups open import group-theory.commutative-monoids open import group-theory.groups open import group-theory.monoids open import group-theory.semigroups open import lists.concatenation-lists open import lists.lists open import ring-theory.rings open import ring-theory.semirings open import univalent-combinatorics.cartesian-product-types open import univalent-combinatorics.dependent-function-types open import univalent-combinatorics.dependent-pair-types open import univalent-combinatorics.equality-finite-types open import univalent-combinatorics.finite-types
Idea
A finite ring is a ring where the underlying type is finite.
Definitions
Finite Rings
has-mul-Finite-Ab : {l1 : Level} (A : Finite-Ab l1) → UU l1 has-mul-Finite-Ab A = has-mul-Ab (ab-Finite-Ab A) Finite-Ring : (l1 : Level) → UU (lsuc l1) Finite-Ring l1 = Σ (Finite-Ab l1) (λ A → has-mul-Finite-Ab A) finite-ring-is-finite-Ring : {l : Level} → (R : Ring l) → is-finite (type-Ring R) → Finite-Ring l pr1 (finite-ring-is-finite-Ring R f) = finite-abelian-group-is-finite-Ab (ab-Ring R) f pr2 (finite-ring-is-finite-Ring R f) = pr2 R module _ {l : Level} (R : Finite-Ring l) where finite-ab-Finite-Ring : Finite-Ab l finite-ab-Finite-Ring = pr1 R ab-Finite-Ring : Ab l ab-Finite-Ring = ab-Finite-Ab finite-ab-Finite-Ring ring-Finite-Ring : Ring l pr1 ring-Finite-Ring = ab-Finite-Ring pr2 ring-Finite-Ring = pr2 R finite-type-Finite-Ring : Finite-Type l finite-type-Finite-Ring = finite-type-Finite-Ab finite-ab-Finite-Ring type-Finite-Ring : UU l type-Finite-Ring = type-Finite-Ab finite-ab-Finite-Ring is-finite-type-Finite-Ring : is-finite type-Finite-Ring is-finite-type-Finite-Ring = is-finite-type-Finite-Ab finite-ab-Finite-Ring finite-group-Finite-Ring : Finite-Group l finite-group-Finite-Ring = finite-group-Finite-Ab finite-ab-Finite-Ring group-Finite-Ring : Group l group-Finite-Ring = group-Ab ab-Finite-Ring additive-commutative-monoid-Finite-Ring : Commutative-Monoid l additive-commutative-monoid-Finite-Ring = commutative-monoid-Ab ab-Finite-Ring additive-monoid-Finite-Ring : Monoid l additive-monoid-Finite-Ring = monoid-Ab ab-Finite-Ring additive-semigroup-Finite-Ring : Semigroup l additive-semigroup-Finite-Ring = semigroup-Ab ab-Finite-Ring set-Finite-Ring : Set l set-Finite-Ring = set-Ab ab-Finite-Ring is-set-type-Finite-Ring : is-set type-Finite-Ring is-set-type-Finite-Ring = is-set-type-Ab ab-Finite-Ring
Addition in a ring
module _ {l : Level} (R : Finite-Ring l) where has-associative-add-Finite-Ring : has-associative-mul-Set (set-Finite-Ring R) has-associative-add-Finite-Ring = has-associative-add-Ring (ring-Finite-Ring R) add-Finite-Ring : type-Finite-Ring R → type-Finite-Ring R → type-Finite-Ring R add-Finite-Ring = add-Ring (ring-Finite-Ring R) add-Finite-Ring' : type-Finite-Ring R → type-Finite-Ring R → type-Finite-Ring R add-Finite-Ring' = add-Ring' (ring-Finite-Ring R) ap-add-Finite-Ring : {x y x' y' : type-Finite-Ring R} → Id x x' → Id y y' → Id (add-Finite-Ring x y) (add-Finite-Ring x' y') ap-add-Finite-Ring = ap-add-Ring (ring-Finite-Ring R) associative-add-Finite-Ring : (x y z : type-Finite-Ring R) → Id ( add-Finite-Ring (add-Finite-Ring x y) z) ( add-Finite-Ring x (add-Finite-Ring y z)) associative-add-Finite-Ring = associative-add-Ring (ring-Finite-Ring R) is-group-additive-semigroup-Finite-Ring : is-group-Semigroup (additive-semigroup-Finite-Ring R) is-group-additive-semigroup-Finite-Ring = is-group-additive-semigroup-Ring (ring-Finite-Ring R) commutative-add-Finite-Ring : (x y : type-Finite-Ring R) → Id (add-Finite-Ring x y) (add-Finite-Ring y x) commutative-add-Finite-Ring = commutative-add-Ring (ring-Finite-Ring R) interchange-add-add-Finite-Ring : (x y x' y' : type-Finite-Ring R) → ( add-Finite-Ring (add-Finite-Ring x y) (add-Finite-Ring x' y')) = ( add-Finite-Ring (add-Finite-Ring x x') (add-Finite-Ring y y')) interchange-add-add-Finite-Ring = interchange-add-add-Ring (ring-Finite-Ring R) right-swap-add-Finite-Ring : (x y z : type-Finite-Ring R) → add-Finite-Ring (add-Finite-Ring x y) z = add-Finite-Ring (add-Finite-Ring x z) y right-swap-add-Finite-Ring = right-swap-add-Ring (ring-Finite-Ring R) left-swap-add-Finite-Ring : (x y z : type-Finite-Ring R) → add-Finite-Ring x (add-Finite-Ring y z) = add-Finite-Ring y (add-Finite-Ring x z) left-swap-add-Finite-Ring = left-swap-add-Ring (ring-Finite-Ring R) is-equiv-add-Finite-Ring : (x : type-Finite-Ring R) → is-equiv (add-Finite-Ring x) is-equiv-add-Finite-Ring = is-equiv-add-Ring (ring-Finite-Ring R) is-equiv-add-Finite-Ring' : (x : type-Finite-Ring R) → is-equiv (add-Finite-Ring' x) is-equiv-add-Finite-Ring' = is-equiv-add-Ring' (ring-Finite-Ring R) is-binary-equiv-add-Finite-Ring : is-binary-equiv add-Finite-Ring is-binary-equiv-add-Finite-Ring = is-binary-equiv-add-Ring (ring-Finite-Ring R) is-binary-emb-add-Finite-Ring : is-binary-emb add-Finite-Ring is-binary-emb-add-Finite-Ring = is-binary-emb-add-Ring (ring-Finite-Ring R) is-emb-add-Finite-Ring : (x : type-Finite-Ring R) → is-emb (add-Finite-Ring x) is-emb-add-Finite-Ring = is-emb-add-Ring (ring-Finite-Ring R) is-emb-add-Finite-Ring' : (x : type-Finite-Ring R) → is-emb (add-Finite-Ring' x) is-emb-add-Finite-Ring' = is-emb-add-Ring' (ring-Finite-Ring R) is-injective-add-Finite-Ring : (x : type-Finite-Ring R) → is-injective (add-Finite-Ring x) is-injective-add-Finite-Ring = is-injective-add-Ring (ring-Finite-Ring R) is-injective-add-Finite-Ring' : (x : type-Finite-Ring R) → is-injective (add-Finite-Ring' x) is-injective-add-Finite-Ring' = is-injective-add-Ring' (ring-Finite-Ring R)
The zero element of a ring
module _ {l : Level} (R : Finite-Ring l) where has-zero-Finite-Ring : is-unital (add-Finite-Ring R) has-zero-Finite-Ring = has-zero-Ring (ring-Finite-Ring R) zero-Finite-Ring : type-Finite-Ring R zero-Finite-Ring = zero-Ring (ring-Finite-Ring R) is-zero-Finite-Ring : type-Finite-Ring R → UU l is-zero-Finite-Ring = is-zero-Ring (ring-Finite-Ring R) is-nonzero-Finite-Ring : type-Finite-Ring R → UU l is-nonzero-Finite-Ring = is-nonzero-Ring (ring-Finite-Ring R) is-zero-finite-ring-Prop : type-Finite-Ring R → Prop l is-zero-finite-ring-Prop = is-zero-ring-Prop (ring-Finite-Ring R) is-nonzero-finite-ring-Prop : type-Finite-Ring R → Prop l is-nonzero-finite-ring-Prop = is-nonzero-ring-Prop (ring-Finite-Ring R) left-unit-law-add-Finite-Ring : (x : type-Finite-Ring R) → Id (add-Finite-Ring R zero-Finite-Ring x) x left-unit-law-add-Finite-Ring = left-unit-law-add-Ring (ring-Finite-Ring R) right-unit-law-add-Finite-Ring : (x : type-Finite-Ring R) → Id (add-Finite-Ring R x zero-Finite-Ring) x right-unit-law-add-Finite-Ring = right-unit-law-add-Ring (ring-Finite-Ring R)
Additive inverses in a ring
module _ {l : Level} (R : Finite-Ring l) where has-negatives-Finite-Ring : is-group-is-unital-Semigroup ( additive-semigroup-Finite-Ring R) ( has-zero-Finite-Ring R) has-negatives-Finite-Ring = has-negatives-Ring (ring-Finite-Ring R) neg-Finite-Ring : type-Finite-Ring R → type-Finite-Ring R neg-Finite-Ring = neg-Ring (ring-Finite-Ring R) left-inverse-law-add-Finite-Ring : (x : type-Finite-Ring R) → Id (add-Finite-Ring R (neg-Finite-Ring x) x) (zero-Finite-Ring R) left-inverse-law-add-Finite-Ring = left-inverse-law-add-Ring (ring-Finite-Ring R) right-inverse-law-add-Finite-Ring : (x : type-Finite-Ring R) → Id (add-Finite-Ring R x (neg-Finite-Ring x)) (zero-Finite-Ring R) right-inverse-law-add-Finite-Ring = right-inverse-law-add-Ring (ring-Finite-Ring R) neg-neg-Finite-Ring : (x : type-Finite-Ring R) → neg-Finite-Ring (neg-Finite-Ring x) = x neg-neg-Finite-Ring = neg-neg-Ring (ring-Finite-Ring R) distributive-neg-add-Finite-Ring : (x y : type-Finite-Ring R) → neg-Finite-Ring (add-Finite-Ring R x y) = add-Finite-Ring R (neg-Finite-Ring x) (neg-Finite-Ring y) distributive-neg-add-Finite-Ring = distributive-neg-add-Ring (ring-Finite-Ring R)
Multiplication in a ring
module _ {l : Level} (R : Finite-Ring l) where has-associative-mul-Finite-Ring : has-associative-mul-Set (set-Finite-Ring R) has-associative-mul-Finite-Ring = has-associative-mul-Ring (ring-Finite-Ring R) mul-Finite-Ring : type-Finite-Ring R → type-Finite-Ring R → type-Finite-Ring R mul-Finite-Ring = mul-Ring (ring-Finite-Ring R) mul-Finite-Ring' : type-Finite-Ring R → type-Finite-Ring R → type-Finite-Ring R mul-Finite-Ring' = mul-Ring' (ring-Finite-Ring R) ap-mul-Finite-Ring : {x x' y y' : type-Finite-Ring R} (p : Id x x') (q : Id y y') → Id (mul-Finite-Ring x y) (mul-Finite-Ring x' y') ap-mul-Finite-Ring = ap-mul-Ring (ring-Finite-Ring R) associative-mul-Finite-Ring : (x y z : type-Finite-Ring R) → Id ( mul-Finite-Ring (mul-Finite-Ring x y) z) ( mul-Finite-Ring x (mul-Finite-Ring y z)) associative-mul-Finite-Ring = associative-mul-Ring (ring-Finite-Ring R) multiplicative-semigroup-Finite-Ring : Semigroup l multiplicative-semigroup-Finite-Ring = multiplicative-semigroup-Ring (ring-Finite-Ring R) left-distributive-mul-add-Finite-Ring : (x y z : type-Finite-Ring R) → mul-Finite-Ring x (add-Finite-Ring R y z) = add-Finite-Ring R (mul-Finite-Ring x y) (mul-Finite-Ring x z) left-distributive-mul-add-Finite-Ring = left-distributive-mul-add-Ring (ring-Finite-Ring R) right-distributive-mul-add-Finite-Ring : (x y z : type-Finite-Ring R) → mul-Finite-Ring (add-Finite-Ring R x y) z = add-Finite-Ring R (mul-Finite-Ring x z) (mul-Finite-Ring y z) right-distributive-mul-add-Finite-Ring = right-distributive-mul-add-Ring (ring-Finite-Ring R)
Multiplicative units in a ring
module _ {l : Level} (R : Finite-Ring l) where is-unital-Finite-Ring : is-unital (mul-Finite-Ring R) is-unital-Finite-Ring = is-unital-Ring (ring-Finite-Ring R) multiplicative-monoid-Finite-Ring : Monoid l multiplicative-monoid-Finite-Ring = multiplicative-monoid-Ring (ring-Finite-Ring R) one-Finite-Ring : type-Finite-Ring R one-Finite-Ring = one-Ring (ring-Finite-Ring R) left-unit-law-mul-Finite-Ring : (x : type-Finite-Ring R) → Id (mul-Finite-Ring R one-Finite-Ring x) x left-unit-law-mul-Finite-Ring = left-unit-law-mul-Ring (ring-Finite-Ring R) right-unit-law-mul-Finite-Ring : (x : type-Finite-Ring R) → Id (mul-Finite-Ring R x one-Finite-Ring) x right-unit-law-mul-Finite-Ring = right-unit-law-mul-Ring (ring-Finite-Ring R)
The zero laws for multiplication of a ring
module _ {l : Level} (R : Finite-Ring l) where left-zero-law-mul-Finite-Ring : (x : type-Finite-Ring R) → Id (mul-Finite-Ring R (zero-Finite-Ring R) x) (zero-Finite-Ring R) left-zero-law-mul-Finite-Ring = left-zero-law-mul-Ring (ring-Finite-Ring R) right-zero-law-mul-Finite-Ring : (x : type-Finite-Ring R) → Id (mul-Finite-Ring R x (zero-Finite-Ring R)) (zero-Finite-Ring R) right-zero-law-mul-Finite-Ring = right-zero-law-mul-Ring (ring-Finite-Ring R)
Rings are semirings
module _ {l : Level} (R : Finite-Ring l) where has-mul-Finite-Ring : has-mul-Commutative-Monoid (additive-commutative-monoid-Finite-Ring R) has-mul-Finite-Ring = has-mul-Ring (ring-Finite-Ring R) zero-laws-mul-Finite-Ring : zero-laws-Commutative-Monoid ( additive-commutative-monoid-Finite-Ring R) ( has-mul-Finite-Ring) zero-laws-mul-Finite-Ring = zero-laws-mul-Ring (ring-Finite-Ring R) semiring-Finite-Ring : Semiring l semiring-Finite-Ring = semiring-Ring (ring-Finite-Ring R)
Computing multiplication with minus one in a ring
module _ {l : Level} (R : Finite-Ring l) where neg-one-Finite-Ring : type-Finite-Ring R neg-one-Finite-Ring = neg-one-Ring (ring-Finite-Ring R) mul-neg-one-Finite-Ring : (x : type-Finite-Ring R) → mul-Finite-Ring R neg-one-Finite-Ring x = neg-Finite-Ring R x mul-neg-one-Finite-Ring = mul-neg-one-Ring (ring-Finite-Ring R) mul-neg-one-Finite-Ring' : (x : type-Finite-Ring R) → mul-Finite-Ring R x neg-one-Finite-Ring = neg-Finite-Ring R x mul-neg-one-Finite-Ring' = mul-neg-one-Ring' (ring-Finite-Ring R) is-involution-mul-neg-one-Finite-Ring : is-involution (mul-Finite-Ring R neg-one-Finite-Ring) is-involution-mul-neg-one-Finite-Ring = is-involution-mul-neg-one-Ring (ring-Finite-Ring R) is-involution-mul-neg-one-Finite-Ring' : is-involution (mul-Finite-Ring' R neg-one-Finite-Ring) is-involution-mul-neg-one-Finite-Ring' = is-involution-mul-neg-one-Ring' (ring-Finite-Ring R)
Left and right negative laws for multiplication
module _ {l : Level} (R : Finite-Ring l) where left-negative-law-mul-Finite-Ring : (x y : type-Finite-Ring R) → mul-Finite-Ring R (neg-Finite-Ring R x) y = neg-Finite-Ring R (mul-Finite-Ring R x y) left-negative-law-mul-Finite-Ring = left-negative-law-mul-Ring (ring-Finite-Ring R) right-negative-law-mul-Finite-Ring : (x y : type-Finite-Ring R) → mul-Finite-Ring R x (neg-Finite-Ring R y) = neg-Finite-Ring R (mul-Finite-Ring R x y) right-negative-law-mul-Finite-Ring = right-negative-law-mul-Ring (ring-Finite-Ring R) mul-neg-Finite-Ring : (x y : type-Finite-Ring R) → mul-Finite-Ring R (neg-Finite-Ring R x) (neg-Finite-Ring R y) = mul-Finite-Ring R x y mul-neg-Finite-Ring = mul-neg-Ring (ring-Finite-Ring R)
Scalar multiplication of ring elements by a natural number
module _ {l : Level} (R : Finite-Ring l) where mul-nat-scalar-Finite-Ring : ℕ → type-Finite-Ring R → type-Finite-Ring R mul-nat-scalar-Finite-Ring = mul-nat-scalar-Ring (ring-Finite-Ring R) ap-mul-nat-scalar-Finite-Ring : {m n : ℕ} {x y : type-Finite-Ring R} → (m = n) → (x = y) → mul-nat-scalar-Finite-Ring m x = mul-nat-scalar-Finite-Ring n y ap-mul-nat-scalar-Finite-Ring = ap-mul-nat-scalar-Ring (ring-Finite-Ring R) left-zero-law-mul-nat-scalar-Finite-Ring : (x : type-Finite-Ring R) → mul-nat-scalar-Finite-Ring 0 x = zero-Finite-Ring R left-zero-law-mul-nat-scalar-Finite-Ring = left-zero-law-mul-nat-scalar-Ring (ring-Finite-Ring R) right-zero-law-mul-nat-scalar-Finite-Ring : (n : ℕ) → mul-nat-scalar-Finite-Ring n (zero-Finite-Ring R) = zero-Finite-Ring R right-zero-law-mul-nat-scalar-Finite-Ring = right-zero-law-mul-nat-scalar-Ring (ring-Finite-Ring R) left-unit-law-mul-nat-scalar-Finite-Ring : (x : type-Finite-Ring R) → mul-nat-scalar-Finite-Ring 1 x = x left-unit-law-mul-nat-scalar-Finite-Ring = left-unit-law-mul-nat-scalar-Ring (ring-Finite-Ring R) left-nat-scalar-law-mul-Finite-Ring : (n : ℕ) (x y : type-Finite-Ring R) → mul-Finite-Ring R (mul-nat-scalar-Finite-Ring n x) y = mul-nat-scalar-Finite-Ring n (mul-Finite-Ring R x y) left-nat-scalar-law-mul-Finite-Ring = left-nat-scalar-law-mul-Ring (ring-Finite-Ring R) right-nat-scalar-law-mul-Finite-Ring : (n : ℕ) (x y : type-Finite-Ring R) → mul-Finite-Ring R x (mul-nat-scalar-Finite-Ring n y) = mul-nat-scalar-Finite-Ring n (mul-Finite-Ring R x y) right-nat-scalar-law-mul-Finite-Ring = right-nat-scalar-law-mul-Ring (ring-Finite-Ring R) left-distributive-mul-nat-scalar-add-Finite-Ring : (n : ℕ) (x y : type-Finite-Ring R) → mul-nat-scalar-Finite-Ring n (add-Finite-Ring R x y) = add-Finite-Ring R ( mul-nat-scalar-Finite-Ring n x) ( mul-nat-scalar-Finite-Ring n y) left-distributive-mul-nat-scalar-add-Finite-Ring = left-distributive-mul-nat-scalar-add-Ring (ring-Finite-Ring R) right-distributive-mul-nat-scalar-add-Finite-Ring : (m n : ℕ) (x : type-Finite-Ring R) → mul-nat-scalar-Finite-Ring (m +ℕ n) x = add-Finite-Ring R ( mul-nat-scalar-Finite-Ring m x) ( mul-nat-scalar-Finite-Ring n x) right-distributive-mul-nat-scalar-add-Finite-Ring = right-distributive-mul-nat-scalar-add-Ring (ring-Finite-Ring R)
Addition of a list of elements in an abelian group
module _ {l : Level} (R : Finite-Ring l) where add-list-Finite-Ring : list (type-Finite-Ring R) → type-Finite-Ring R add-list-Finite-Ring = add-list-Ring (ring-Finite-Ring R) preserves-concat-add-list-Finite-Ring : (l1 l2 : list (type-Finite-Ring R)) → Id ( add-list-Finite-Ring (concat-list l1 l2)) ( add-Finite-Ring R (add-list-Finite-Ring l1) (add-list-Finite-Ring l2)) preserves-concat-add-list-Finite-Ring = preserves-concat-add-list-Ring (ring-Finite-Ring R)
Properties
There is a finite number of ways to equip a finite type with the structure of a ring
module _ {l : Level} (X : Finite-Type l) where structure-ring-Finite-Type : UU l structure-ring-Finite-Type = Σ ( structure-abelian-group-Finite-Type X) ( λ m → has-mul-Finite-Ab ( finite-abelian-group-structure-abelian-group-Finite-Type X m)) finite-ring-structure-ring-Finite-Type : structure-ring-Finite-Type → Finite-Ring l pr1 (finite-ring-structure-ring-Finite-Type (m , c)) = finite-abelian-group-structure-abelian-group-Finite-Type X m pr2 (finite-ring-structure-ring-Finite-Type (m , c)) = c is-finite-structure-ring-Finite-Type : is-finite structure-ring-Finite-Type is-finite-structure-ring-Finite-Type = is-finite-Σ ( is-finite-structure-abelian-group-Finite-Type X) ( λ a → is-finite-Σ ( is-finite-Σ ( is-finite-Π ( is-finite-type-Finite-Type X) ( λ _ → is-finite-Π ( is-finite-type-Finite-Type X) ( λ _ → is-finite-type-Finite-Type X))) ( λ m → is-finite-Π ( is-finite-type-Finite-Type X) ( λ x → is-finite-Π ( is-finite-type-Finite-Type X) ( λ y → is-finite-Π ( is-finite-type-Finite-Type X) ( λ z → is-finite-eq-Finite-Type X))))) ( λ a → is-finite-product ( is-finite-is-unital-Finite-Semigroup (X , a)) ( is-finite-product ( is-finite-Π ( is-finite-type-Finite-Type X) ( λ _ → is-finite-Π ( is-finite-type-Finite-Type X) ( λ _ → is-finite-Π ( is-finite-type-Finite-Type X) ( λ _ → is-finite-eq-Finite-Type X)))) ( is-finite-Π ( is-finite-type-Finite-Type X) ( λ _ → is-finite-Π ( is-finite-type-Finite-Type X) ( λ _ → is-finite-Π ( is-finite-type-Finite-Type X) ( λ _ → is-finite-eq-Finite-Type X)))))))
Recent changes
- 2025-02-11. Fredrik Bakke. Switch from
𝔽
toFinite-*
(#1312). - 2024-03-11. Fredrik Bakke. Refactor category theory to use strictly involutive identity types (#1052).
- 2024-02-07. Fredrik Bakke. Deduplicate definitions (#1022).
- 2024-02-06. Fredrik Bakke. Rename
(co)prod
to(co)product
(#1017). - 2023-06-09. Fredrik Bakke. Remove unused imports (#648).